The Effect of Drying Temperature and Concentration of Dextrin on The Quality of Red Beet Instant Drink - Lenni Triani Naibaho; Ismed Suhaidi; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2015)
This study was conducted to determine the effect of drying temperature and concentration of dextrin on the quality of red beet instant drink. This research is using completely randomized design (CRD) with two factors, i. e : drying temperature (S) : (60oC, 70oC, 80oC) and concentration of dextrin (D) : (2%, 4%, 6%, 8%, 10%). The parameters analyzed were yield, water content, ash content, vitamin C content, total soluble solid, solubility, solubility speed, the score value of color and taste, and the hedonic value of flavor and taste. The result showed that drying temperature had highly significant effect on yield, water content, vitamin C content, solubility, solubility speed, the score value of color and taste and the hedonic value of flavor and taste. Concentration of dextrin had highly significant effect on yield, water content, ash content, vitamin C content, total soluble solid, solubility, solubility speed, the score value of color and taste, and the hedonic value of flavor and taste. The interaction between the two factors had highly significant on vitamin C content and the score value of color. Drying temperature of 60oC and concentration dextrin of 10% produced the best quality of red beet instant drink. Keywords :dextrin, drying temperature,instant drink,red beet